2023
DOI: 10.1177/20503121231162354
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with adherence and viral suppression among patients on second-line antiretroviral therapy in an urban HIV program in Kenya

Abstract: Objective: The aim of this study is to estimate the proportion of virologically suppressed People living with HIV on second-line ART and to identify factors associated with virologic suppression. With an increasing population of patients on complex second-line anti retroviral therapy (ART), understanding the factors associated with viral suppression and adherence is critical for ensured longevity of ART. Methods: A retrospective study was conducted of patients on second-line ART in 17 facilities supported by U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Second, our study only considered data from Uganda, and our results may not directly generalize to other settings. However epidemiological patterns reported here are typical of ESA, such as: expansive population pyramids [27], patterns in HIV prevalence by age and gender [44], and gender gaps in suppression levels [12,[33][34][35][36][37][38][39][40]. These observations suggests that the major contributions of individuals aged 25-34 to the burden of viraemia may generalize across the subcontinent.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Second, our study only considered data from Uganda, and our results may not directly generalize to other settings. However epidemiological patterns reported here are typical of ESA, such as: expansive population pyramids [27], patterns in HIV prevalence by age and gender [44], and gender gaps in suppression levels [12,[33][34][35][36][37][38][39][40]. These observations suggests that the major contributions of individuals aged 25-34 to the burden of viraemia may generalize across the subcontinent.…”
Section: Discussionmentioning
confidence: 79%
“…For example, in inland communities, we found that young individuals aged 15-24 constituted approximately two fifths of the census-eligible population, but only one fifth of the population exhibiting viremia. In fact, the lower suppression levels commonly reported among young PLHIV [12,[33][34][35][36][37][38][39][40] are counterbalanced by the small absolute number of young PLHIV. This observation is typically missing from studies supporting prioritization of younger age-groups in ESA based on the UNAIDS targets 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Study findings of cohort study in Africa showed that among PLWHA with ART experience and viral suppression, those who moved to tenofovir/lamivudine/dolutegravir (TLD) maintained viral suppression better than those who persisted on other regimens (8). The HIV program in Kenya reported that second-line ART users had a viral load suppression rate of 90% (9). Findings revealed that among 46.8% of HIV patients on second-line ART, 88.2% achieved viral load suppression (4).…”
mentioning
confidence: 99%